Pengaruh Pelathan Kerja dan Kompensasi Kerja Terhadap Kinerja Karyawan Foodpedia Group Jakarta - Muhammad Husen Bawafi; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of job training and job compensation on the performance of Foodpedia Group Jakarta employees. The population in this study were all employees of the Foodpedia Group Jakarta outlet as many as 100 employees with the measuring instrument used was a questionnaire distributed via google form. The research method used is quantitative method with Non-Probability sampling method Likert scale 1-5. The data processing performed is multiple linear regression analysis and using the F test and T test. The results of the hypothesis in this study are; that job training has a significant effect on employee performance, that work compensation has a significant effect on employee performance, while the results of the f test of both variables have a simultaneous effect.